Gambaran Pengetahuan dan Sikap Remaja Tentang Jajanan Sehat di SMP Negeri 1 Mamuju - Asmariani, Andi Nur; Nurbaya, Nurbaya; Najdah, Najdah; Irwan, Zaki; Al-Fath, Muhammad Dzulifsal (Badan Riset dan Inovasi Daerah Sulawesi Tengah, 2025)
Previous research has shown that 72.8% of school children’s snack samples in six major cities in Indonesia contained harmful substances. This study aimed to describe students’ knowledge and attitudes toward healthy snacks at SMP Negeri 1 Mamuju. A descriptive design was used with a total sample of 192 students selected through proportional random sampling from grades VII and VIII. Data were collected using a structured questionnaire measuring levels of knowledge and attitudes toward healthy snacks. The results showed that the majority of respondents had low knowledge (65.1%), followed by moderate knowledge (26.0%) and high knowledge (8.9%). Nevertheless, most students had a positive attitude toward healthy snacks (68.2%), followed by moderate (22.4%) and poor attitudes (9.4%). Relationship analysis revealed that all students with high knowledge also had positive attitudes, while those with low knowledge were still dominated by positive attitudes, although a considerable proportion exhibited moderate and poor attitudes. These findings indicate a gap between knowledge and attitudes, which could potentially affect the consistent application of healthy snack consumption behavior. Integrated nutrition education interventions, along with school canteen supervision and the habituation of healthy eating practices, are needed to improve knowledge while maintaining students’ positive attitudes.